San Basilio frente al mar. La variante estética del argumento del diseño - Sebastián, Adrián Pradier (Cauriensia, 2022)
The aim of this study consists of an approach to the aesthetic argument in the framework of theism. The starting point is an apparent tension between two concepts of beauty, located in the framework of St. Basil's exegetical commentary on the biblical account of the six days of Creation. Accordingly, we perceive two ways of appreciating the world in an aesthetic manner: functional and disinterested. If the first perspective underpins the design argument, the second raises the possibility of an aesthetic variant closely linked to the former. Keeping in mind the questions raised by St. Basil, the second section contains two parts: a brief genealogy of the design argument, with the aim of finding the theoretical roots of the aesthetic variant, and the presentation of the argument by Frederick R. Tennant, its most recognizable proponent. Having reviewed the meaning, object and scope of the argument, the third section analyzes the state of art, focusing on its main theoretical challenges, and we delve into one of the most recent contributions, signed by the theologians Richard Swinburne and Kai-man Kwan. Lastly, some conclusions are presented.